INTRACRANIAL COMPLICATONS OF CHRONIC SUPPURATIVE OTITIS MEDIA - Khan, Hidayat Ullah; Saleem, Muhammad; Shahabi, Isteraj; Ismail, Muhammad; Ashfaq, Muhammad; Ahmad, Naseer (Journal of Postgraduate Medical Institute, 2011)
Objective: To study the presentations of various intra cranial complications of chronic suppurative otitis media (SOM) . Material and Methods: This prospective and descriptive study was conducted in the department of ENT, Lady Reading Hospital Peshawar from April 2006 to march 2007. All the cases with suspected intra cranial complications were admitted to the department and assessed clinically and radiologically. Audiological, and laboratory investigations were done as well. Results: Out of 50 cases 36 were male and 14 female ranging from 10-40 years in age. Complications like meningitis and brain abscesses were more common in males in the 2 from atticoantral diseases. The main presenting features were foul smelling otorrhea, headache, and fever, neck stiffness, chloestosteatoma and granulations in the ear. Meningitis (46%), temporal lobe abscess (36%) and extra dural abscess (14%) were the commonest complications. Burr hole aspiration, for intra cranial abscess and radical/ modified radical mastoidecomy for SOM were the main surgical procedure carried out for these patients. Conclusion: Otogenic intra cranial complications like meningitis and brain abscesses are still common in spite of advances in the medical sciences. Complications are common in 2 complication followed by brain abscess Burr whole aspiration with modified, radical mastoidectomy is the main stay of treatment along with parenteral antibiotics. nd and 3rd decade of life (72%). Most of the complications werend and 3rd decade of life. Meningitis is the commonest